2009
DOI: 10.1351/pac-con-08-10-03
|View full text |Cite
|
Sign up to set email alerts
|

Steric and electronic effects in SN2 reactions

Abstract: This article gives an overview of recently published literature on the factors that govern S N 2 reactivity. By comparing reactivity in solution with that in the isolated gas phase, it has become possible to dissect the contribution of the solvent from that of the intrinsic molecular properties. This has proven to be an extremely important and fruitful step forward in obtaining key knowledge not available before. The gas-phase studies have made it clear that organic chemists need to revise radically their conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…The S N 2 reaction profile is characterized by two ion‐molecule energy minima: one occurring before the transition state (TS), and one after, while progressing along the reaction coordinate . Several recent reviews on S N 2 reactions are available . The complexation energies and S N 2 reactions of X – + CH 3 X systems (where X = F, Cl, Br, and I) have previously been calculated at the G2(+) level of theory.…”
Section: Introductionmentioning
confidence: 99%
“…The S N 2 reaction profile is characterized by two ion‐molecule energy minima: one occurring before the transition state (TS), and one after, while progressing along the reaction coordinate . Several recent reviews on S N 2 reactions are available . The complexation energies and S N 2 reactions of X – + CH 3 X systems (where X = F, Cl, Br, and I) have previously been calculated at the G2(+) level of theory.…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers, gas phase aliphatic S N 2 reactivity has been systematically addressed by applying various quantum chemical methods and approaches. These studies have demonstrated how trends in reactivity can be examined in terms of physical observables and other well-defined parameters, relating these to periodic table order. The prototype reaction, Y + CH 3 −X Y− CH 3 + X has been studied in great detail, and it has been shown that the critical energy ( E # , the energy difference between the transition state and the isolated reactants) necessary to adapt the transition state geometry has two contributions, one from the thermochemical driving force (the bond dissociation energy difference between the C–Y bond to be formed and the C–X bond to be broken) and another from an intrinsic factor that is equal to the average critical energy of the two identity reactions, i.e., the corresponding reactions in which the nucleophile and nucleofuge are identical: X + CH 3 −X X− CH 3 + X and Y + CH 3 −Y Y− CH 3 + <...…”
Section: Introductionmentioning
confidence: 99%
“…Further, enhanced reactivity is also observed for nucleophiles carrying a lone pair of electrons adjacent to the nucleophilic center (α effect). However, the intrinsic properties of the reactants are strongly influenced by the solvent; thus, experiments in the condensed phase are, by definition, affected by solvent effects which may obscure the intrinsic features of the reactants. The latter can be elucidated by means of gas-phase experiments in which both the elementary steps and the nature of the “bare” reactants are studied at a strictly molecular level, thus leading to a better understanding of the individual effects which control the reaction efficiency. This holds also true for various C–N coupling reactions mediated by gaseous ions bearing an M–C bond. Fundamental insight has been achieved since the first studies of gas-phase S N 2 reactions in the 1970s performed by the groups of Bohme and Brauman. Two general types have been investigated both experimentally and computationally: (i) an anionic nucleophile Y – reacts with a neutral substrate (eq ) and (ii) a neutral nucleophile Y interacts with an electrophilic cation (eq ). RX + normalY RY + normalX RX + + Y RY + + normalX …”
Section: Introductionmentioning
confidence: 99%